Computerised temperature measurement of multiple cold room / Anuar Abu Bakar - Abu Bakar, Anuar (1994)
Basically this project is the temperature measurement of the multiple cold room. The range of temperature to be measured is between -40°C and 6(f C. In order to suit with this range of temperature, RS590 is used as temperature sensor. This temperature is men displayed by using a personal computer. Quick basic high level language is used as a program in order to display the measurement.